PERTUMBUHAN DAN PRODUKSI MIKROALGA PORPHYRIDIUM AERUGINEUM (Rhodopyceae) PADA SALINITAS DAN FOTOPERIODA BERBEDA. - Aras Mulyadi (Program Pascasarjana Universitas Riau, 2007)
The growth and production of Porphyridiuni aerugineuni has been studied at different salinity: 0 % o, 5 %o, 10 %o and photoperiod: 1Oh/14h, 14h/1Oh, 18h/6h. Bacth culture of red ? nicroalgae has been apllied on F/2 Guillard medium and 25 °C. The salinity has influenced the growth of Porphyridium aerugineum. The optimal growth of this rhodophyceae was on freshwater. While the increase of salinity has decreased the cells concentration; but has increased the growth rate and the production. The prolongation of photophase has increased the growth and production of this rhodophyceae. But the cells concentration and dry weight of Porphyridium aerugineum was better on photoperiod of 14W /10 than 18h/6h.